Reflexões acerca do processo de alfabetização na perspectiva histórico-crítica: experiência no Programa Institucional de Bolsas de Iniciação à Docência, UFT - Câmpus Universitário de Miracema - Sousa, Joana Marinho de (Universidade Federal do Tocantins, 2025)
The Institutional Teaching Initiation Scholarship Program (PIBID), in the educational context, provided undergraduate students in the Pedagogy degree course at the Federal University of Tocantins - Miracema Campus, with initial access to the teaching space. A bibliographical survey was carried out based on Saviani (2011), Gasparin (2012), Goulart, Garcia and Corais (2019), Miranda (1987), Smolka (1987), Lorenzetti and Delizoicov (2001). It is understood that for children to be able to enter the literacy process, it is necessary for the teacher to have a perspective as a theoretical foundation, after all, pedagogical work is the theoretical-practical relationship. Initially, the children are observed so that teaching strategies can then be created that are appropriate to their context. Based on this, it is understood that one of the perspectives that formed the theoretical basis for the activities carried out at the field school was the Historical-Critical perspective, which understands the child as a whole. The activities were structured according to Gasparin's Didactics (2012), as follows: initial social practice, problematization, instrumentalization and catharsis. This made it possible to recognize children as builders of scientific knowledge.